PENGARUH PERSEPSI KARYAWAN MENGENAI WHISTLEBLOWING SYSTEM, SISTEM PENGENDALIAN INTERNAL DAN MORALITAS TERHADAP PENCEGAHAN FRAUD PADA PT. SEAFOOD INSPECTION LABORATORY - Luh Putu Asahi Artha Prasasthy; Putu Nuniek Hutnaleontina (Hita Akuntansi dan Keuangan, 2021)
This study aims to examine the effect of employee perceptions regarding the Whistleblowing system, internal control system and morality on fraud prevention at PT. Seafood Inspection Laboratory. Collecting data on this study through interview and questionnaires and using Likert scale to measure. The sampling in this study used the Saturated Sample method were 99 employees of PT. Seafood Inspection Laboratory. This research used multiple linear regression test data analysis technique. Data were analyzed using SPSS 21 for Windows software. The results of this study indicate that employee perceptions of the Whistleblowing system have no effect on fraud prevention, internal control systems and morality have a positive and significant effect on fraud prevention (fraud).